INNOVATIVE STRATEGIES IN PEDAGOGY, TRANSLATION THEORY, AND FOREIGN LANGUAGE TEACHING WITHIN THE CONTEXT OF EDUCATIONAL REFORMS IN THE REPUBLIC OF UZBEKISTAN - Azatova Shakhzada,; Muratova Dilorom Mahmudovna, (TADQIQOTLAR, 2025)
Annotation:  This  article  examines  contemporary  approaches  to  linguistic education and translator training amidst widespread digitalization. Special attention is paid  to  the  implementation  of  state  programs  in  the  Republic  of  Uzbekistan,  the introduction  of blended  learning technologies  (Blended  Learning), the  use  of  CAT tools, and the CLIL methodology. The paper also analyzes the transformation of the roles of the teacher and the translator within the new educational paradigm.